(untitled) (Research, Society and Development, 2022)
In 2020, it was observed in Brazil and other countries of the world, the spread of a new virus that took everyone by surprise and caused incalculable damage, the Virus SARS, cause of Covid-19. In that cruel context, many activities were severely affected, among them those related to the school environment. This context has also brought to schools enormous challenges to the teaching and learning process. However, with the emergence of vaccines, the pandemic situation improved significantly and, gradually, life was "returning to normal". In an attempt to promote a return to school life, the Federal Government decided, among other measures, to apply the SAEB test as early as 2021. However, even in an unfavourable reality, especially when it comes to participating in a large external evaluation, a small rural school from Ceará managed to achieve a successful result in its IDEB that year, showing that the integration between student and school occurred despite the scenario. Thus, the study aimed to identify the factors that can explain the success achieved by the school in improving the IDEB. For this, legal documents were consulted, as well as on-site research. The results obtained show that the significant growth in the school approval rate, the improvement in proficiency in the mathematics test and the frequency above the minimum required, even in a pandemic scenario, consistently explain the success achieved by the school and, thus, these results can contribute to the preparation for the new challenges.